A large neglected pleomorphic adenoma of the lung: Report of a rare case. (June 2014) - Gakidis, Ioannis; Mihos, Petros T; Chatziantoniou, Christos; Stamatelopoulos, Athanasios; Eftychiadis, Christos; Mantas, Constantinos
Primary pleomorphic adenomas of the lung are very rare tumors that have peculiar clinical and oncologic features. We report here on the diagnostic and therapeutic approach for a patient with a large neglected pulmonary pleomorphic adenoma that presented initially as pneumonia.